2011
DOI: 10.1002/lsm.21103
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of endotracheal tube biofilms using antimicrobial photodynamic therapy

Abstract: Background Ventilator-associated pneumonia (VAP) is reported to occur in 12 to 25% of patients who require mechanical ventilation with a mortality rate of 24 to 71%. The endotracheal (ET) tube has long been recognized as a major factor in the development of VAP since biofilm harbored within the ET tube become dislodged during mechanical ventilation and have direct access to the lungs. The objective of this study was to demonstrate the safety and effectiveness of a non-invasive antimicrobial photodynamic therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 23 publications
0
30
0
3
Order By: Relevance
“…The non- Candida pathogens T. mucoides and K. ohmeri were inactivated by APDT, with reductions of 0.85 log 10 and 0.84 log 10 , respectively [63]. Biel et al demonstrated that MB-mediated APDT is highly effective in the photoeradication of multispecies bacterial biofilms (multidrug-resistant P. aeruginosa and MRSA) [64, 65]. A significant decrease in CFU/mL (>6 log 10 units) was achieved when 300  μ g/mL MB and a light dose of 60 J/cm 2 (diode laser, 664 nm) were used.…”
Section: Antimicrobial Photodynamic Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…The non- Candida pathogens T. mucoides and K. ohmeri were inactivated by APDT, with reductions of 0.85 log 10 and 0.84 log 10 , respectively [63]. Biel et al demonstrated that MB-mediated APDT is highly effective in the photoeradication of multispecies bacterial biofilms (multidrug-resistant P. aeruginosa and MRSA) [64, 65]. A significant decrease in CFU/mL (>6 log 10 units) was achieved when 300  μ g/mL MB and a light dose of 60 J/cm 2 (diode laser, 664 nm) were used.…”
Section: Antimicrobial Photodynamic Therapymentioning
confidence: 99%
“…A significant decrease in CFU/mL (>6 log 10 units) was achieved when 300  μ g/mL MB and a light dose of 60 J/cm 2 (diode laser, 664 nm) were used. The reduction was >7 log 10 units when 500  μ g/mL MB and two light doses of 55 J/cm 2 separated by a 5-minute break were used [64, 65]. Meire et al observed a statistically significant 1.9 log 10 reduction in the viable counts of E. faecalis biofilms treated with 10 mg/mL MB and exposed to a soft laser of an output power of 75 mW (660 nm) for 2 min [66].…”
Section: Antimicrobial Photodynamic Therapymentioning
confidence: 99%
“…These fi ndings were consistent with those found in the literature (Feldman et al 1999 ). Further In vitro preclinical studies of the methylene blue based photosensitizer to photoablate polymicrobial antibiotic resistant gram-negative and gram-positive bacterial biofi lms in an endotracheal tube/ventilator model demonstrated a the more than 3 log 10 reduction from baseline (p < 0.005) (Biel et al 2011b ). Based on these preclinical studies, a multi-institutional FDA IDE approved randomized controlled clinical trial is presently in progress to demonstrate the effi cacy of aPDT in the reduction of ventilator associated pneumonia as compared to standard of care therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Use of PDT for bacterial biofilms led to an almost complete disruption and clearance of P. aeruginosa [36], a reduction of greater than 6-7 log 10 units depending on treatment protocol for P. aerugenosa and methicillin-resistant S. aureus [37,38], and a reduction of 1.9 log 10 in the viable counts of E. faecalis [39]. Use of PDT for C. albicans biofilms led to a reduction of 0.33-0.85 log 10 [40].…”
Section: Antibiofilm Treatmentsmentioning
confidence: 99%